PP2A delays APC/C‐dependent degradation of separase‐associated but not free securin. (29th April 2014) - Hellmuth, Susanne; Böttger, Franziska; Pan, Cuiping; Mann, Matthias; Stemmann, Olaf
Abstract The universal triggering event of eukaryotic chromosome segregation is cleavage of centromeric cohesin by separase. Prior to anaphase, most separase is kept inactive by association with securin. Protein phosphatase 2A (PP2A) constitutes another binding partner of human separase, but the functional relevance of this interaction has remained enigmatic. We demonstrate that PP2A stabilizes separase‐associated securin by dephosphorylation, while phosphorylation of free securin enhances its polyubiquitylation by the ubiquitin ligase APC/C and proteasomal degradation. Changing PP2A substrate phosphorylation sites to alanines slows degradation of free securin, delays separase activation, lengthens early anaphase, and results in anaphase bridges and DNA damage. In contrast, separase‐associated securin is destabilized by introduction of phosphorylation‐mimetic aspartates or extinction of separase‐associated PP2A activity. G2‐ or prometaphase‐arrested cells suffer from unscheduled activation of separase when endogenous securin is replaced by aspartate‐mutant securin. Thus, PP2A‐dependent stabilization of separase‐associated securin prevents precocious activation of separase during checkpoint‐mediated arrests with basal APC/C activity and increases the abruptness and fidelity of sister chromatid separation in anaphase.